2015
DOI: 10.1107/s205252061500342x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a threefold rotation axis in α-Fe2O3and α-Cr2O3crystals

Abstract: The crystal structure of α-Fe2O3 and α-Cr2O3 is usually described with the corundum-type trigonal crystal structure based on the space group R3¯c. There are, however, some observations of the magnetic ordering of both α-Fe2O3 and α-Cr2O3 that are incompatible with the trigonal symmetry. We show experimental evidence based on X-ray powder diffraction and supported by transmission electron microscopy that the symmetry of the crystal structure of both α-Fe2O3 and α-Cr2O3 is monoclinic and it is described with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…High-resolution synchrotron radiation diffraction measurements were performed with a synthetic commercial -Fe 2 O 3 powder sample provided by Aldrich. The measurements were performed at the ESRF beamline ID22 operating at the wavelength 0.40086 Å , as described in Stę kiel et al (2015). Synchrotron radiation diffraction measurements were performed with -Fe 2 O 3 at several temperature steps by warming from room temperature to 1053 K. After reaching every temperature step by the hot-air blower sensor there was a 12 min waiting time before thermal equilibration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution synchrotron radiation diffraction measurements were performed with a synthetic commercial -Fe 2 O 3 powder sample provided by Aldrich. The measurements were performed at the ESRF beamline ID22 operating at the wavelength 0.40086 Å , as described in Stę kiel et al (2015). Synchrotron radiation diffraction measurements were performed with -Fe 2 O 3 at several temperature steps by warming from room temperature to 1053 K. After reaching every temperature step by the hot-air blower sensor there was a 12 min waiting time before thermal equilibration.…”
Section: Methodsmentioning
confidence: 99%
“…Recent structural studies have shown that the crystal structure of -Fe 2 O 3 is monoclinic at room temperature (Przeniosło et al, 2014). The monoclinic symmetry of the -Fe 2 O 3 crystal structure is compatible with the canted antiferromagnetic ordering (Przeniosło et al, 2014;Stę kiel et al, 2015), while the trigonal corundum-type crystal structure is not. There are also other arguments supporting the hypothesis of a monoclinic symmetry of the -Fe 2 O 3 crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…[43] The monoclinic distortion can be used to explain the odd magnetic order in these materials that lacks a three-fold axis. Similarly, a small distortion away from R-3 in MnTiO3 could be used to explain the existence of the weak anomaly at TN in εca but not εac, the pre-edge feature observed in the O-K edge found using electron energy loss spectroscopy that was not seen in other ilmenites [44], and could also account for all of the unexpected features found in the second harmonic generation data in the paramagnetic and high-field regimes.…”
Section: -Discussionmentioning
confidence: 99%
“…Recent high resolution SR diffraction studies reported a monoclinic crystal structure (space group C2/c) of α‐Fe 2 O 3 instead of the rhombohedral (R3¯c) one . The monoclinic α‐Fe 2 O 3 structure shows small deviations as compared with the trigonal one , and these fine details can be neglected in the present study. The description of the present X‐ray powder diffraction studies of the texture induced by the magnetic field is simpler for the trigonal (R3¯c) structure.…”
Section: Introductionmentioning
confidence: 64%
“…The crystal structure of hematite, α‐Fe 2 O 3 , is described by using the trigonal space group R3¯c . Recent high resolution SR diffraction studies reported a monoclinic crystal structure (space group C2/c) of α‐Fe 2 O 3 instead of the rhombohedral (R3¯c) one . The monoclinic α‐Fe 2 O 3 structure shows small deviations as compared with the trigonal one , and these fine details can be neglected in the present study.…”
Section: Introductionmentioning
confidence: 73%